Wisisi Sebagai Media Pendidikan Multikultural: Studi Kasus Pertunjukan Massal Pelajar Papua: Indonesia - Muhammad Ilham Mustain Murda; Suwarjiya; Indar Sabri; Arif Hidajad; Gita Kinanthi Purnama Asri Adinda (PANGGUNG, 2026)
In contemporary Papua, Wisisi has moved beyond ritual settings into educational and public performance, opening a culture-based pathway for multicultural learning. This study analyzes how mass Wisisi performance functions as embodied pedagogy among students in Papua. It uses a qualitative approach combining digital ethnography and autoethnographic reflection. Data were drawn from audiovisual documentation of the 2025 MURI record performance in Wamena, a schoolchildren's Wisisi performance in Tiom, a Kompas.com report, supporting documents, and interview material with artist and music producer Asep Nayak. The data were collected through digital observation, repeated viewing, note-taking, and source comparison, then interpreted thematically through embodied pedagogy and multicultural education. The findings show that synchronized movement, collective rhythm, and spatial restructuring transform Wisisi into a living medium for solidarity, cultural transmission, and interethnic learning. This article recommends culturally rooted performance as a pedagogical infrastructure for Papuan education.